Effect of early protected weight bearing in fractures of shaft of femur - Pillai, Manju G. (International Journal of Research in Orthopaedics, 2019)
Background: Fracture shaft of femur is a common and major musculoskeletal injury and in most of the cases the patients are immediately brought to hospitals for specialist orthopaedic management. The purpose of this study was to evaluate the effectiveness of early protected weight bearing in fractures of shaft of femur. Methods: This was observational study conducted on 35 patient’s hospital with transverse fracture mid-shaft of femur, between March 2007 and July 2011. Patients with high velocity trauma, with transverse fracture of mid shaft of femur amenable to closed reduction and interlocking intramedullary nailing and otherwise healthy individuals were included in this study. The preoperative parameters were recorded included age, gender, side of the fracture and medical history. All patients were operated on second day of admission. Results: A total of 35 consecutive cases were included, 34 patients were males and 1 was female. In 74% cases closed intramedullary nailing given excellent healing of fracture, in 14% cases healing was good, in 6% cases it was average and 6% cases poor healing was observed. Conclusions: Our study demonstrate that this method provides anatomical reduction and maintenance of femur length and early ambulation which promotes fracture healing by a stable internal fixation allowing micro motion at fracture site enhancing callous formation.